Heat Mapping and Plastic Strain Radius Modeling of Dual-Tool Friction Stir Welds 6061 Aluminum Alloy Plate Using FEM - Rikko Putra Youlia; Diah Utami; Dedik Romahadi; Tang Yishuang (International Journal of Innovation in Mechanical Engineering and Advanced Materials, 2024)
This study investigates the effects of Dual-Tool Friction Stir Welding (DT-FSW) parameters on the weld quality of 8 mm thick 6061 aluminum alloy plates, specifically focusing on the elimination or minimization of the "pass-overlap zone" that’s a gap typically observed at the mid-section of the weld cross-section resembling characteristics of the Heat-Affected Zone (HAZ). To address ongoing debates regarding the optimal joint performance concerning this overlap, symmetric increases in the dimensions of both FSW tools were implemented to analyze resultant temperature fields and plastic strain adaptations at the weld interfaces. Simulation visualizations were conducted with tool density variations at intervals of 0.2 mm and 0.4 mm. Results indicate that increasing tool density, thereby reducing the distance between tool surfaces, leads to a decrease in peak temperatures generated during welding. This reduction in temperature correlates with a more uniform distribution of plastic strain rates across all layers of the material—upper, middle, and lower—with the leading edge exhibiting the most significant improvement in strain uniformity. Conversely, during the stabilization phase, a decrease in tool density (S) results in a reduction of the maximum equivalent plastic strain rate. These findings suggest that careful adjustment of tool density in DT-FSW processes can enhance weld quality by promoting more uniform mechanical and thermal properties across the joint.